How excitation-emission matrices have revolutionised multi-way data analyses – A tutorial for multi-way EEM-based calibration method developments - Antonio, Marina (2025)
For many years, excitation-emission matrix (EEM) fluorescence spectroscopy has been a compelling analytical technique, fostering the development of multidimensional data analysis-based methods. Its applications span diverse fields, including analytical chemistry and biological, food, and environmental sciences, which have been extensively documented in the scientific literature. EEM spectroscopy stands out for its versatility, affordability, and exceptional capacity to provide rich analytical insights, making it a preferred choice for investigations requiring higher-order data analysis. While second-order data analysis based on EEM fluorescence spectroscopy has been widely explored, generating third-order data from EEM remains a challenging and spotlighted research area.This tutorial intends to trace the evolution of multi-way data analysis in recent years, focusing on applying multidimensional fluorescence in analytical contexts. It delves into the critical issues, emerging trends, and challenges in analytical calibration method developments. Moreover, our comprehensive assessment encompasses the instrumental, methodological, and practical aspects of multi-way data applications, providing tailored guidance to empower readers in overcoming obstacles and advancing their research endeavours..